Worldviews about the self mediate the impact of immature and mature defense styles on posttraumatic symptoms in bereaved parents. Issue 6 (3rd July 2022) - Ferrajão, Paulo
Abstract: The present study analyzed the mediating role of assumptive worldviews on the effect of defense mechanisms on post-traumatic stress symptoms (PTS) in bereaved parents. Sample included a convenience sample of 153 bereaved parents and a control group of 157 nonbereaved parents. Structural equation modeling was conducted to examine our hypotheses. Bereaved parents presented higher levels of PTS and more negative assumptions compared to nonbereaved participants. Worthiness of the self mediated the effect of both immature and mature defense styles on PTS levels, and neurotic defense style directly predicted PTS levels.